A Multiscale Structural Analysis of Soft and Hard Coal Deposits in Deep High-Gas Coal Seams. (18th March 2021) - Yuan, Anying; Fu, Guangsheng; Hou, Junling
Abstract : In recent years, with the increases in coal mining depths, the risk of coal seam outburst occurrences has increased. Therefore, it is of major significance to study the multiscale structures of soft and hard coal deposits in order to prevent and control the coal and gas outbursts. In this research investigation, soft and hard coal multiscale structures were comprehensively examined using various laboratory methods. The results revealed the following: (1) From a macrostructural aspect, the physical and mechanical properties of the soft coal were weaker than those of the hard coal. It was found that the majority of the examined specimens were characterized by scaly structures without blocks larger than 50 mm. The hard coal was observed to be mainly massive with only a small part being clastic. Therefore, the structural characteristics were considered to be stable. (2) From a microstructural perspective, the surfaces of the soft coal specimens were observed to be rough. The pores were found to be more developed, with the edge of pores being mainly hackly. At the same time, fractures were also relatively developed, showing good connectivity. (3) From a micropore structural perspective, it was found that the BET-specific surface areas and BJH-specific surface areas of the soft coal specimens were higher than those of the hard coal specimens, which indicated that the gas adsorption and diffusion migration abilities of the soft coal were greater than those of the hard coal. (4) It was suggested from the study results that the ventilation and gas extraction processes should be strengthened in the mining activities of coal seams with high, soft stratification content. At the same time, the methods used for water injection modification should be enhanced in order to improve the mechanical stability of soft coal. Consequently, the instantaneous released gases will be decelerated, and the occurrences of coal and gas outburst events in mine working faces can be prevented.